Evaluasi Tata Kelola Teknologi Informasi Menggunakan Kerangka Kerja Cobit 5 di SMK XYZ - Susilowati, Feni; Saputro, Wahju Tjahjo; Pasa, Ike Yunia (INTEK : Jurnal Informatika dan Teknologi Informasi, 2023)
The application of IT in the field of education has emerged, such as in SMK Muhammadiyah Purworejo. The presence of IT in the organization helps improve school progress both in operational activities and services. However, in the school, there are still some parts that have not been managed properly. Problems that exist in SMK Muhammadiyah Purworejo such as school management activities that are not yet well structured, for example: not having a school payment system, not having a library system service, and the school’s vision, mission, and goals that have not been implemented properly. This study attempts to evaluate governance using the COBIT version 5 framework to assist in guiding the management of the school. researchers used the APO domain (sub domain APO-02 and APO-07) and BAI (sub domain BAI06). The selected domain will evaluate for managing strategy, HR, and managing change. Researchers obtained school data from interviews, observations, and distributing questionnaires to respondents (there were 18 people). The results of the questionnaire distribution show that the Purworejo Muhammadiyah Vocational School agrees to hold follow-up changes in the school so that it can realign according to the school’s vision, mission, and goals. The average of the APO-02 subdomain is 0.365; APO-07 of 0.157; and BAI-06 of 0.147. The domain gap is still at level 0 (Incomplete Process). The results of the BAI-06 and APO-02 sub-domains are still too far from the expected target, which is at level 3 (Established Process), while APO-07 is the expected target at level 4 (Predictable Process). Recommendations given by researchers from the BAI06 domain require improvement of business processes both from services, and school policies, and always evaluating these changes. APO-02 recommendations on strategic management in terms of improving student services and designing long-term strategies for schools. Meanwhile, APO-07 continues to develop the quality of its human resources by increasing its skills and expertise.